Correction: Long non-coding RNA MEG3 inhibits cell proliferation, migration, invasion and enhances apoptosis in non-small cell lung cancer cells by regulating the miR-31-5p/TIMP3 axis. Issue 35 (5th June 2020) - Li, Kui; Wang, Xiaodan; Huang, Zhen; Xu, Hui; Zheng, Songbai; Qiu, Yurong
Abstract : Correction for 'Long non-coding RNA MEG3 inhibits cell proliferation, migration, invasion and enhances apoptosis in non-small cell lung cancer cells by regulating the miR-31-5p/TIMP3 axis' by Kui Li et al., RSC Adv., 2019, 9, 38200–38208, DOI: ; 10.1039/C9RA07880K .